Case report of multiple pustules of the bilateral lower limbs caused by a granulocyte colony‐stimulating factor‐producing solid pseudopapillary tumour of the pancreas. (1st October 2017) - Iwata, Y.; Kobayashi, T.; Kuroda, M.; Mizoguchi, Y.; Arima, M.; Numata, S.; Watanabe, S.; Yagami, A.; Matsunaga, K.; Sugiura, K.
Summary: Here we report a rare case of neutrophilic dermatoses related to a granulocyte colony‐stimulating factor (G‐CSF)‐producing solid pseudopapillary tumour (SPT). The patient was a 39‐year‐old woman presenting with scattered pustules and crusts of the palms, heels and thighs and plaques of the bilateral lower legs. The skin biopsy revealed dense neutrophil infiltration in the epidermis to the dermis. A pancreatic head tumour was detected using computed tomography. A pathological examination of the resected specimen suggested an SPT. As the skin eruption promptly disappeared after SPT resection, we hypothesized that SPT secretes growth factors including epidermal growth factor (EGF) and G‐CSF. The SPT cells stained positive for both EGF and G‐CSF tumour cells. The serum levels of interleukin (IL)‐6 and IL‐10 and tumour necrosis factor‐α were within normal limits before and after the SPT resection. In contrast, the serum IL‐8, EGF and G‐CSF levels decreased after the SPT resection. This is a rare case of neutrophilic dermatoses related to a G‐CSF‐producing SPT. The present case suggests that physicians should be aware that a G‐CSF‐producing tumour is a differential diagnosis to consider in patients with unusual aseptic pustulosis.